Determinants of Postgraduates' Use of Electronic Information Resources in Federal Universities in Southern Nigeria. Issue 3 (1st September 2020) - Azonobi, I. N.; Uwaifo, S. O.; Tella, Adeyinka
Abstract: This study explored the determinants of postgraduates' use of electronic information resources in federal universities in southern Nigeria. The purpose was to identify the factors that influence user behavior and ascertain how factor like self-efficacy could increase the use of electronic information resources. Descriptive survey method was adopted for the study. The sample size of 591 post graduates was selected through purposive sampling technique. The study used a researchers' designed questionnaire for the collection of data which was analyzed using frequency counts, mean, and standard deviation. The findings of the study revealed that psychological factors such as trust on the information source and perceived usefulness, and self-efficacy and social factors like referral from course-mates and lecturers as the factors that influenced the use of electronic information resources. High self-efficacy level increased the use of electronic information resources among the respondents. Based on the findings, the study recommends that universities should improve their subscription to various electronic information resources through their libraries and such should be from renowned publishers of high impact to increase their usage.